The Influence of the Cooperative Learning Model on Students' Absorption in Islamic Education Subjects at SMP Negeri 1 Panga - Erlina (Jurnal Profesi Guru Indonesia, 2024)
The Influence of Cooperative Learning Model on Students' Absorption in Islamic Religious Education Subjects at SMP Negeri 1 Panga, Aceh Jaya Regency", with the aim of knowing the cooperative learning process and to improve students' absorption in Islamic religious education subjects at school. This study was conducted using library research and field research. This study uses a quantitative descriptive approach, namely describing and interpreting according to the data obtained in the field and also using frequency distribution to calculate the results of the questionnaire distributed to respondents. While for data collection using observation techniques, interviews, questionnaires and documentation. The results of this study show that almost all (92%) students have high absorption of Islamic Religious Education subjects, very few (8%) students have moderate absorption of Islamic Religious Education subjects and none at all (0%) students have no absorption of Islamic Religious Education subjects, thus meaning that students of SMP Negeri 1 Panga class VIII.2 have high absorption of Islamic Religious Education subjects. In addition to having a high absorption capacity, students are expected to be willing to practice the teachings of Islam that they receive from Islamic Religious Education at school, which they then apply in their daily lives.